Families calliphoridae and mesembrinellidae - Wolff, Marta; Kosmann, Cecilia [UNESP] (Magnolia Press, 2016)
Calliphoridae and Mesembrinellidae (Diptera, Oestroidea) are very common groups of flies, the Calliphoridae with worldwide distribution and over 1,000 described species, while the Mesembrinellidae are restricted to the Neotropical Region and founded mainly in areas with undisturbed native vegetation. This catalogue presents two families: Calliphoridae, with 4 subfamilies, 31 species distributed in 12 genera, and Mesembrinellidae, with 7 genera and 21 species.
Keywords: Calliphoridae; Catalogue; Colombia; Distribution; Mesembrinellidae